PERUBAHAN KURIKULUM PADA PROSES PEMBELAJARAN - Erin Aprillia; Cut Nurhayati; Anjani Putri Belawati Pandiangan (CV Putra Publisher, 2023)
This research is the result of combining several articles, journals and books that discuss the impact of curriculum changes on the learning process. In its journey, Indonesia has experienced various changes in the curriculum model since independence. According to law No. 20 of 2003, curriculum is a set of plans and setting goals, content and learning materials as well as the methods used as guidelines for organizing learning in achieving national education goals. A good curriculum is a curriculum that is developed according to the living conditions of students. Develop abilities or competencies to achieve goals as needed. Of course, the curriculum is refined year after year. Because technology is growing. If no changes to the curriculum are made, the quality of education in Indonesia will continue to decline because the learning system only implements an outdated or old curriculum. This article wants to describe in more detail about how curriculum changes in the teaching and learning process experienced by teachers or students.